Role of Brushing and Occlusal Forces in Non-Carious Cervical Lesions (NCCL) - Sadaf, Durre (Int J Biomed Sci, 2014)
OBJECTIVE: To assess the association of occlusal forces and brushing with non-carious cervical lesions (NCCL). METHODOLOGY: It was a Cross-sectional study. The study was conducted in Dental clinics, Department of Surgery, The Aga Khan University Hospital Karachi. The study duration was from 1(st) January 2009 to 28(th) Feb 2009. Ninety patients visiting dental clinic were examined clinically. Presence of Non- carious cervical lesions, broken restorations, fractured cusps, presence of occlusal facets, brushing habits, Para functional habits were assessed. All the relevant information and clinical examination were collected on a structured Performa and was analyzed using SPSS version 14.0. . Chi square χ(2) test was applied to assess association among different categorical variables. RESULT: Twenty three (26%) females and 67 (74%) males were included in the study. Thirty five of them (38.9%) were found to have Non-carious cervical lesions. Presence of NCCL has no association with gender (P value 0.458). A significant association was found between NCCL and teeth sensitivity (P value 0.002).The association between use of hard tooth brush and Non-carious cervical lesions was found significant (P value <0.001). However the association among Non-carious cervical lesions and fractured cups, broken restoration, teeth grinding, jaw clenching, pan chalia chewing and frequency of teeth brushing were insignificant. CONCLUSION: Hard tooth brushing and teeth sensitivity have significant association with Non-carious cervical lesions. The role of occlusal wear in the formation of NCCL is not significant.